Occurrence of Second Mesio-buccal Canal in Maxillary First Permanent Molar: A CBCT Study - Shrestha, Sandhya; Sapkota, Manish Raj; Shah, Ankit; Rajbhandari, Santosh; Sapkota, Pratyush (Orthodontic Journal of Nepal, 2017)
Introduction: Complexity in root canal morphology leads to chances of failure in endodontic treatment due to missed canal. Availability of Cone-beam Computed Tomography (CBCT) has contributed to assess second mesiobuccal canals in maxillary first molars. Objective: To study the presence of second mesiobuccal (MB2) canals, classify morphology of canals according to Vertucci’s classification and to measure the distance between MB1 and MB2 canals. Materials & Method: 72 CBCT scans including 115 permanent maxillary first molars were evaluated by endodontist and oral radiologist separately using Dicom software to study the mesiobuccal root canal morphology. Oral radiologist and endodontist individually evaluated the scans through coronal, axial and oblique views to study canal configurations. Vertucci’s Classification was used to classify the canal configurations. Statistical tests were done to assess the gender variation and arch side difference. Result: Among 115 images evaluated; 30.4% samples had second mesiobuccal canal. The most common canal configuration was Type I (60.9 %) in mesiobuccal root. The mean distance between MB1 and MB2 canals was 2.39 mm in female and 2.56 mm in male. Conclusion: The occurrence of second canal in mesiobuccal root of maxillary permanent molar is considerable in Nepali patients. CBCT can be an effective tool to detect MB2 canal and other complexities of root canal system to achieve clinical success